STRATEGI PENGEMBANGAN KOMPETENSI UNTUK MEWUJUDKAN SMART ASN DI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KOTA BANDUNG - Nuraeni, Sonia (Prodi Administrasi Publik FISIP UNPAS, 2021)
Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) is the spearhead of ASN development, because of it’s role as a Regional Apparatus Organization that manages all ASN, therefore the quality of ASN is determined by the quality of BKPSDM. Competency development includes education and training, internships, seminars, and courses. This study uses a qualitative research method with a descriptive approach aimed at explaining a symptom, phenomenon or social reality in the field. The results of the study reveal that competency development to realize SMART ASN has been carried out quite well in the environment of BKPSDM Kota Bandung, the less than optimal implementation of the competency development program is due to the Covid-19 pandemic which requires changing all concepts outside the network to be in the network, in this case BKPSDM Kota Bandung is not ready to make changes to the entire program in a short time. Nevertheless, there are still competency development programs that are carried out online using video conferencing facilities. Competency Development Strategy to Realize SMART ASN at BKPSDM Kota Bandung, based on the Rancangan Pembangunan Jangka Menengah Daerah 2018-2023, with a mission to Realize Servant, Effective, Efficient, and Clean Governance. The competency development program in the BKPSDM Kota Bandung environment consists of Tugas belajar dan izin belajar, managerial, socio-cultural, and technical education and training.